2018
DOI: 10.26808/rs.ph.i8v2.02
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Musculoskeletal Disorders Among Tailors

Abstract: Work related musculoskeletal disorders are a group of painful disorders due to repeated basis or overuse for days, months or years and those effects bones, muscles, joints, ligaments, tendons, nerves, bursa and blood vessels are stressed and traumatized and those body tissues ultimately become damaged. Aim of the present study is to identify the prevalence of work related musculoskeletal disorders among tailors. This cross sectional study was conducted among 100 tailors and use of the standardized tool Nordic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(9 reference statements)
0
1
1
Order By: Relevance
“…This is likely to result in increased prevalence of neck and shoulder pains among self-employed workers in the country. Our survey found a lower prevalence of neck and or shoulder pains compared to a study in India (91 and 88% in neck and shoulder,respectively) [ 45 ]. However, our finding is higher than that of 49.7% neck and 41.6% shoulder pain prevalence in study in Iran [ 21 ] and 31.67 and 38.33% prevalence of pain in neck and shoulder, respectively, from the report in India [ 46 ].…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…This is likely to result in increased prevalence of neck and shoulder pains among self-employed workers in the country. Our survey found a lower prevalence of neck and or shoulder pains compared to a study in India (91 and 88% in neck and shoulder,respectively) [ 45 ]. However, our finding is higher than that of 49.7% neck and 41.6% shoulder pain prevalence in study in Iran [ 21 ] and 31.67 and 38.33% prevalence of pain in neck and shoulder, respectively, from the report in India [ 46 ].…”
Section: Discussioncontrasting
confidence: 62%
“…According to the study in Finland, upper back pains, including neck and shoulder were more likely to increasein the newly employed workers because of a lack of acclimatization to the work environment, particularly to a high workload. Conversely, other investigations have shown that a longer duration of employment increases the risk of neck and shoulder pains [ 27 , 45 , 49 ]. This disagreement may be due to variations in the designs of the studies (prospective follow up versus cross-sectional), study populations (self-employed versus employed by others) and the nature of the work environments (informal tailor shops versus registered garment factories).…”
Section: Discussionmentioning
confidence: 99%